The Relationship between Blood Gas Analysis Profile and the Outcome of Severe COVID-19 Patients - Helena Sembai; Sulina Yanti Wibawa; Irda Handayani; Darmawaty ER. Rauf (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2023)
Coronaviruses commonly infect the respiratory tract, leading to severe pneumonia. Respiratory problems cause numerous acid-base disorders in 2019 Coronavirus Disease (COVID-19) patients. Several studies have explored laboratory biomarkers used in the management and prognosis of COVID-19 patients during this pandemic; however, only a few focused on blood gas analysis. Determine the blood gas analysis pattern and its association with the outcome of severe COVID-19 patients treated in the Intensive Care Unit (ICU). This retrospective cohort study used secondary data from patients with severe COVID-19 treated in the ICU of Hasanuddin University Hospital between January and December 2021. There was a higher number of male (58.8%) compared to female patients (41.5%), with a mean age of 62 years. Respiratory alkalosis was the most prevalent blood gas disorder (24.4%). Metabolic alkalosis was a blood gas disorder with the highest number of recovery/improvement outcomes (8 patients). There was no significant relationship between blood gas analysis results and the outcome of severe COVID-19. In addition, no specific pattern was found in the results of blood gas analysis. Respiratory alkalosis was the most frequent blood gas disorder detected in these patients.